2015
DOI: 10.1002/jcp.25010
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin‐Mediated Changes in Human Tendon Cells

Abstract: Statins are among the most widely prescribed drugs worldwide. Numerous studies have shown their beneficial effects in prevention of cardiovascular disease through cholesterol‐lowering and anti‐atherosclerotic properties. Although some statin patients may experience muscle‐related symptoms, severe side effects of statin therapy are rare, primarily due to extensive first‐pass metabolism in the liver. Skeletal muscles appear to be the main site of side effects; however, recently some statin‐related adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Besides the increased MMP expression in this study, we also found a decreased expression of both collagen type 1 and 3. This has previously been shown after lovastatin treatment on human tendon fibroblasts in 2D culture, an effect that was assumed to be mediated via prenylation of GTPases [17]. Atorvastatin has also been shown to have a negative effect on collagen type 1 gene expression in rat Achilles tendons [10].…”
Section: Discussionmentioning
confidence: 69%
“…Besides the increased MMP expression in this study, we also found a decreased expression of both collagen type 1 and 3. This has previously been shown after lovastatin treatment on human tendon fibroblasts in 2D culture, an effect that was assumed to be mediated via prenylation of GTPases [17]. Atorvastatin has also been shown to have a negative effect on collagen type 1 gene expression in rat Achilles tendons [10].…”
Section: Discussionmentioning
confidence: 69%
“…Lovastatin (LVT), a highly lipophilic drug (log P =4.3) isolated from a fungus of Aspergillus terreus , belongs to the class of cholesterol-lowering drugs and is the first clinically used statin. 1 It is a prodrug which lowers the cholesterol level through reversible competitive inhibition of 3-hydroxy-3-methyl-glutaryl coenzyme A reductase, an enzyme involved in biosynthesis of cholesterol. However, LVT exhibits poor oral bioavailability (<5%) because of its poor water solubility (0.4×10 −3 mg/mL) and short half-life (1–2 hours).…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with this possibility, a number of laboratory studies have demonstrated a direct impairment of collagen metabolism in response to statin exposure, including reduced type I collagen levels and increased expression and activity of several matrix metalloproteinases. [ 7 , 8 , 9 ] However, the best evidence available to date comprises a propensity-score matched study of over 500,000 statin-users in the UK: in that study, statin use was not associated with an increased risk of Achilles tendon rupture. [ 10 ] In their discussion, the authors noted that their study could not exclude the possibility that statins might lead to milder tendon injury such as tendinopathy.…”
Section: Introductionmentioning
confidence: 99%